Highly selective inhibition of butyrylcholinesterase by a novel melatonin–tacrine heterodimers. Issue 4 (May 2013) - Zawadzka, Anna; Łozińska, Iwona; Molęda, Zuzanna; Panasiewicz, Mirosława; Czarnocki, Zbigniew
Abstract: Novel inhibitors of cholinesterases, especially butyrylcholinesterase (BuChE), were obtained by coupling melatonin–tacrine heterodimers via the carbamate bond. Compounds14a‐i possessed potent cholinesterase inhibitory activity (with IC50 values as low as 1.18 nm for acetylcholinesterase (AChE) and 0.24 nm for butyrylcholinesterase (BuChE)). These heterodimers exhibit selectivity toward BuChE, being from 4‐ to 256‐fold more active toward BuChE than AChE, but still acting as better AChE inhibitors than tacrine4 .